Storm time current distribution in the inner equatorial magnetosphere: THEMIS observations. Issue 6 (17th June 2016) - Yang, Y. Y.; Shen, C.; Dunlop, M.; Rong, Z. J.; Li, X.; Angelopoulos, V.; Chen, Z. Q.; Yan, G. Q.; Ji, Y.
Abstract: For the first time, the current density distribution in the inner equatorial magnetosphere ranging from 4 to 12 RE ( RE is the Earth radius, 6371 km) has been obtained by using Time History of Events and Macroscale Interactions during Substorms (THEMIS) (P3, P4, and P5) three point magnetic measurements. This study mainly focuses on the storm events when the constellation of the three THEMIS spacecraft has relatively small separation distance. Two cases with different storm activities are first displayed to illustrate the effectiveness of the method. The inner magnetospheric equatorial current distribution ranging from 4 to 12 RE is shown through statistical analysis. The features of current density are separately analyzed for the storm main phase and the recovery phase. The statistical study reveals that with increasing radial distance the predominant ring current density reverses from Eastward (below r  = 4.8 RE, where r is the geocentric radial distance) to Westward, but that the distribution behaves differently for the two phases of activity. During the main phase, both the westward and eastward current are enhanced by added signal and are more dynamic so that both radial profile and magnetic local time (MLT) structure is obscured. During the recovery phase, the radial profile of the westward current is smooth and peaks, then falls, between r  = 5–7.5 RE showing some MLT dependence in this region. Beyond r  = 7.5 RE, the current is lower and nearly constant and shows little MLT variation. The results also suggest that the change from eastward to westward current depends on the storm phase and hence storm activity. Key Points: Gives the current distribution in the inner magnetospheric equatorial region Obtains the current distribution features during storm main phase and the recovery phase Reveals the eastward‐to‐westward transition movement of the ring current